Development of CENTS-RAS system using PLC improve water quality - Masrul Nizam Mahmod; Mastura Ramli; Ahmad Daud Om (International Journal of Technology, Innovation and Humanities, 2020)
Cheap Efficient Nursery Tank System - Recirculating Aquaculture System (CENTS-RAS) is an alternative hatchery system used in most places in Tanjung Demong Terengganu. Waste trap (Wastrap) is a system on CENTS-RAS to dispose of sewage and needs to be opened according to schedule to ensure water quality is at a good level. This requires employees to open the wastrap manually and in an orderly manner. Problems occur when the frequency does not occur regularly. Design and construction smart wastewater controlled by Programmable Logic Controller (PLC) to output electrical actuator ball valve fit in inlet water and wastrap installed in CENTS-RAS for maintaining good water quality. Disposal of dirty water as well as conversion with clean livestock water is systematically controlled based on the programmed time. Previously using manual methods for wastrap opening, fish survival and growth probably limit the production potential is around 78% -85%. After construction with smart system automatically regular scheduling with 4 time interval methods that have been set will work 24 hours a day for 50 days to ensure the conversion rate and life is high. Effectiveness water quality control were higher by implementing new design using automated methods.